2009
DOI: 10.1007/s11692-009-9058-7
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Success and Sexual Selection in Wild Eastern Tiger Salamanders (Ambystoma t. tigrinum)

Abstract: Variation in reproductive success is most pronounced in species with strongly biased operational sex ratios, prominent sexual dimorphisms, and where mate competition and choice are likely. We studied sexual selection in eastern tiger salamanders (Ambystoma t. tigrinum) and examined the role of body size on reproductive success. We genotyped 155 adults and 1,341 larvae from 90 egg masses at six microsatellite loci. Parentage analyses revealed both sexes engaged in multiple matings, but was more common among fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 78 publications
3
14
0
Order By: Relevance
“…This form of BSSD suggests that female-larger SSD in S. keyserlingii develops to resolve 'intersexual ontogenetic conflict' (Badyaev 2002) by allowing smallsized males to swell their whole body during the aquatic phase, as much as large-sized females. By contrast, in ambystomatids distributed widely in North America (i.e., a counterpart of hynobiids distributed in Asia), sexual selection on body size is lacking (Williams and DeWoody 2009). This may lead to the absence of substantial attention to the interaction of size dimorphism to a difference in shape even in Hynobius and Triturus species with drastically increased BSSD traits during the aquatic phase (Hasumi and Iwasawa 1990;Malmgren and Thollesson 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This form of BSSD suggests that female-larger SSD in S. keyserlingii develops to resolve 'intersexual ontogenetic conflict' (Badyaev 2002) by allowing smallsized males to swell their whole body during the aquatic phase, as much as large-sized females. By contrast, in ambystomatids distributed widely in North America (i.e., a counterpart of hynobiids distributed in Asia), sexual selection on body size is lacking (Williams and DeWoody 2009). This may lead to the absence of substantial attention to the interaction of size dimorphism to a difference in shape even in Hynobius and Triturus species with drastically increased BSSD traits during the aquatic phase (Hasumi and Iwasawa 1990;Malmgren and Thollesson 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Another measure of population health is estimates of physical abnormalities. Amphibian abnormality rates have recently been reported to exceed the expected rates of 0-5% (Johnson et al, 2002;Williams and DeWoody, 2009). Although some hellbender abnormalities are thought to result from intraspecific confrontations, abnormalities are reported at rates much higher than expected (Miller and Miller, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a number of studies on a variety of species and taxa have now found that both males and females increase their RS with the number of mates (e.g., 9-11), a result contrary to those predicted by Bateman gradients. Moreover, in some of these species, there is little or no difference between the sexes (11), and in at least one species of katydid, females have steeper gradients than males (12). Moreover, it is also well known that females in the majority of sexual species mate multiply and often take the lead in seeking additional copulations with different males, a behavior that also violates Bateman's predictions (5).…”
mentioning
confidence: 99%